2017
DOI: 10.1177/1744629516674066
|View full text |Cite
|
Sign up to set email alerts
|

Identity constructions and transition to adulthood for young people with mild intellectual disabilities

Abstract: This article explores the self-constructions of young adults with mild intellectual disabilities in talk about their everyday living and how parents and professionals construct young adults with disabilities in talk about their involvement in transition processes. The analysis is related to an interpretive tradition and conducted based on individual interviews with four young adults with mild intellectual disability, five parents of young adults with mild intellectual disabilities and five professionals in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
1
14
0
4
Order By: Relevance
“…Aside from themes specific to having an intellectual disability, the participants' perspectives were generally very similar to those one might expect to record amongst typically developing young adults (Furstenberg, Kennedy, McLoyd, Rumbaut, & Settersten, ; Nelson & Luster, ). As only one other paper could be found that directly explored this population's attitudes towards growing up and adulthood (Midjo & Aune, ), there is very little extant literature with which to compare our findings. In some ways, for example, this similarity was unexpected, as previous research has suggested that young adults with mild intellectual disabilities may have different concerns to their typically developing peers at this stage in life (Forte, Jahoda, & Dagnan, ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Aside from themes specific to having an intellectual disability, the participants' perspectives were generally very similar to those one might expect to record amongst typically developing young adults (Furstenberg, Kennedy, McLoyd, Rumbaut, & Settersten, ; Nelson & Luster, ). As only one other paper could be found that directly explored this population's attitudes towards growing up and adulthood (Midjo & Aune, ), there is very little extant literature with which to compare our findings. In some ways, for example, this similarity was unexpected, as previous research has suggested that young adults with mild intellectual disabilities may have different concerns to their typically developing peers at this stage in life (Forte, Jahoda, & Dagnan, ).…”
Section: Discussionmentioning
confidence: 97%
“…Yet, as suggested by Midjo and Aune (), today's young adults with intellectual disabilities have been brought up in time that places great emphasis on equal rights and opportunities. Consequently, it may not be surprising that many young people with disabilities have grown to expect that they will lead “ordinary” lives in the long run.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis was inspired by the tradition of meaning interpretation, which goes beyond reformulation of subjects' experiences and meanings through deeper and critical interpretations of the text (Brinkmann and Kvale 2015;Midjo and Aune 2018). Hence, the results are thematically presented together with emic (Hammersley and Atkinson 2007) interpretations.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies could be found that focussed on young people with intellectual disabilities’ perspectives on their own transition experiences. First, Midjo and Aune (2016) interviewed four Norwegian young adults with mild intellectual disabilities in an attempt to investigate their self‐constructions when conversing about their daily lives. The authors found that undertaking housework was symbolic of the female participants’ independence and self‐ascribed adult identity.…”
Section: Introductionmentioning
confidence: 99%